Prime Minister Decree No. 1478/2013 On Forming A Committee to study the Utilization of Black Sands = قرار رئيس مجلس الوزراء رقم 1478 لسنة 2013 بتشكيل لجنة لدراسة موضوع استغلال الرمال السوداء / Prime Minister. - Egypt. Prime Minister (2025)
Prime minister’s decree no. 1478 of the year 2013 – قرار رئيس مجلس الوزراء رقم 1478 لسنة 2013